Effects of selectively triggered photothermal particles on shape memory polymer composites: An investigation on structural performance, thermomechanical characteristics and photothermal behaviour. (December 2019) - Herath, Madhubhashitha; Epaarachchi, Jayantha; Islam, Mainul; Yan, Cheng; Zhang, Fenghua; Leng, Jinsong
Light-activated shape memory polymer composites (LASMPCs) have the ability to facilitate breakthrough technological advancements in aerospace and space engineering applications since the shape memory effect can be remotely controlled by a light beam. Introduction of rare-earth organic complexes–based photothermal fillers such as Nd(TTA)3 Phen and Yb(TTA)3 Phen into thermally activated shape memory polymers has been reported as a convenient and commercially available approach to prepare light-activated shape memory polymer composites. Such light-activated shape memory polymer composites undertake selective photothermal stimulation due to light and applicable for macroscale and microscale applications. This article presents the effects of added rare-earth organic complexes of Nd(TTA)3 Phen and Yb(TTA)3 Phen, as well as glass fibre reinforcements on structural performance and shape memory behaviour of light-activated shape memory polymer composites. The physical and mechanical properties, as well as thermomechanical, shape memory, and photothermal behaviours, were systematically investigated. It has been found that the combination of photothermal fillers and glass fibre reinforcements has enhanced the capacity of light-activated shape memory polymer composites to apply for a wider range of large-scale engineering applications.